Formulation and Antibacterial Activity of Porang (Amorphophallus muelleri Blume) Extract Gel Against Propionibacterium acne - Nurshalati Tahar; Dwi Wahyuni; Rabiatul Adawiyah; Khaerani; Munifah Wahyuddin (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2023)
Introduction: The increase in bacterial resistance to antibiotics provides an opportunity to obtain antibacterial compounds from natural ingredients. Porang is a plant belonging to the Araceae family that has potential against Propionibacterium acne. Aims: This study aims to determine the effectiveness of the preparation of porang tuber extract gel against Propionibacterium acne. Methods: The porang were extraction by maceration using ethanol. The extract porang were made gel with various concentration and evaluation their stability and antibacterial activity using disc diffusion method. Result: The hedonic test showed no significant differenece each of formula and stable during storage in two weeks. On the other hand, only formula F2 and F3 can inhibit of Propionibacterium acnee. Conclusion: The porang extract can made of gel and good stability. The formula F2 and F3 have antibacterial activity.